Improving the percentage of HIV tests offered to patients admitted to an acute hospital trust with community-acquired pneumonia. Issue 4 (17th December 2020) - McGuinness, Rachel; Keevil, Harry; Sharif, Adam; Lau, Ting Kwan; Crookes, William; Bhamm, Roma; Ali, Salma; Payne, Victoria; Hollinshead, Leanna; Cundy, Karen; Choudhury, Aklak
Abstract : Young people and adults diagnosed with an HIV indicator condition should be offered an HIV test (NICE [National Institute of Clinical Excellence] guidance). Community-acquired pneumonia (CAP) is considered to be an HIV indicator condition as it has an undiagnosed HIV prevalence of 0.76%. We observed however, that the offer of HIV testing to patients with radiologically diagnosed CAP remained low even after a senior respiratory physician review. Our aim was to improve the percentage of patients being offered an HIV test with CAP requiring hospital admission across four acute medical wards at Royal Derby Hospital within 12 months. We identified several key steps in the process. These included the identification of CAP, the role of the medical clerking team and the respiratory infections nursing team that manage pneumonia admissions. After collecting baseline data and staff interviews, we conducted seven plan-do-study-act (PDSA) interventions. These included; iterative communication, educational interventions, system changes that involved a direct HIV test offering by our respiratory infection team and the addition of an HIV test to the electronic CAP bundle. Data collected from 177 patients were analysed over a period of one year. The main outcome measure of the project 'Did patients with a diagnosis of CAP on admission have a documented HIV test offered?' improved from 28% during the first cycle of data collection to 76.4% during the final cycle. Patients were more likely to be offered an HIV test if they had no comorbidity compared with those with a diagnosis of asthma or chronic obstructive pulmonary disease. Our most impactful PDSA interventions were the respiratory infection nurses directly offering an HIV test to patients and adding HIV to the electronic ordering CAP bundle. Our quality improvement programme has shown that educational, communication and system changes can help improve the uptake of HIV testing. Education on HIV testing is now part of our induction programme for new doctors and we are using a new CAP bundle to help streamline the request of HIV testing at the first clinician clerking. Our dedicated respiratory infection nursing team also ensures that patients with CAP have a documented offer of an HIV test.